A comparison of large language models and model-driven reverse engineering for reverse engineering - Siala, Hanan; Lano, Kevin (Frontiers in Computer Science, 2025)
Large language models (LLMs) have been extensively researched for programming-related tasks, including program summarisation, over recent years. However, the task of abstracting formal specifications from code using LLMs has been less explored. Precise program analysis approaches based on model-driven reverse engineering (MDRE) have also been researched, and in this paper we compare the results of the LLM and MDRE approaches on tasks of abstracting Python and Java programs to the OCL formal language. We also define a combined approach which achieves improved results.